Business Model Innovation and Decision-Making for the Productive Sector in Times of Crisis - Terán-Bustamante, Antonia; Martínez Velasco, Antonieta Teodora (My University, 2022)
The pandemic caused by COVID-19 has affected all companies and their business models. For this reason, firms have needed to redesign these models, focusing on customer value proposition. The purpose of this research is to analyze Business Model Innovation (BMI) for decision-making. The methodological strategy is carried out through Bayesian networks. A model is made in which the main elements that make up a BMI are identified and quantified, which impact better decision-making to properly manage the proposal value for customers, technology, and achieve innovation. Evidence shows that the construction of BMI requires a model that mainly considers the relationships between variables such as knowledge architecture, implementation operation, change and evolution, and agile response. BMI will apply to organizations to the extent that it contemplates variables related to customer service and attention, as well as those related to innovation in organizations, attention, and those related to innovation in organizations. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: International business enterprises; International economic integration; Globalization